THE DETERMINANTS OF THE LEVEL OF FINANCIAL LITERACY IN TURKEY - Düzakın, Hatice; Yılmaz, Süreyya (Copernican Journal of Finance & Accounting, 2021)
The main objective of this study was to explain individuals’ financial literacy levels through socioeconomic and demographic variables. A random sample of 1000 participants was recruited from Turkey. As an indicator of the financial literacy level, a measure with three constructs was adopted: financial attitude, financial behaviour and financial knowledge. Logit model was estimated from these explanatory variables: gender, age, marital status, number of family members, education, income, number of persons with income, household income and working conditions. In the logit model results, the effect of gender, age and education was statistically significant and positive. The results emphasized that there is a relationship between financial literacy level and gender, age and education. Additionally, the results of this study indicated that the level of financial literacy is 52.9% in Turkey.